IMPROVEMENT OF SANITARY STATE OF SOILS IN THE POPULATED AREAS USING BIOREMEDIATION METHOD - O.O. Kulahin (Проблеми екології та медицини)
The aim of the research. Evaluation of the effectiveness of different types of biological products for purification of the soil, contaminated by oil products (OP) in the laboratory experiment and field conditions. Materials and methods. To achieve this aim, the experiment was performed in laboratory and field conditions, using two different types of biological preparations – a solid mix (No.1) and an aqueous solution for irrigation (No.2). In the field experiments, the destructive activity of the preparation was studied on the industrial sites of power electric substations in Dnepropetrovsk, polluted with booster oil (BO). In the laboratory experiment 3 variants of soil pollution with disel fuel (DF) with adding of different concentrations of the sorbent were used. Research results. During the research it was found that on the sites of power substations, BO contents in all investigated samples taken from the surface (0-30 cm) and from deeper (30-60 cm) soil layers significantly decreased and made up 895.52-3988.03 mg/ kg, as compared with the analysis of samples taken in autumn of 2015 – 10 978.04-94 715.85 mg/kg, respectively. During the laboratory experiment, it was found that the greater the concentration of the sorbent, the more effective is its destructive activity, as a result of which on the 60th day of the experiment, the residual concentration of DF was 11.66-53.29% of the initial one. Conclusions. The use of biological products in the liquid form, considering regularities of processes of fluid filtration in soils is appropriate in the contamination of surface layers (0-30 cm), in low – up to 12 000 mg/kg, concentrations of OP. In significant amounts of OP (up to 94.7 g/kg) and contamination of deeper soil layers, the most effective is the use of destructors on a solid matrix. Application of preparations No.1 and No.2 into the soil, contaminated with OP, in exposure of 2-9 months ensures its purification with the efficiency from 95.8 to 46.3%.